Energy Tree Dynamics of Smart Grid Based on Industrial Internet of Things - Yang Wang; Peng Zeng; Haibin Yu; Yanyu Zhang; Xu Wang (International Journal of Distributed Sensor Networks)
Service-oriented architectures make establishing comprehensive profiles of smart factories feasible. In this paper, an energy tree model is used to describe a profile that shapes energy system dynamics. The energy tree shows an overall and detailed profile that combines information communication technologies and ontology knowledge bases. A 7-level network protocol defines sustainable communication services for accumulating local information to maintain the global energy tree in real time. The communication protocol manages everchanging temporal and spatial misalignments by aligning groups of energy resources that are temporally or spatially related. Meanwhile, correlated domain information regarding industrial processes is formulized into ontology models. Ontology-based semantic contexts allocate knowledge-supported attributes to energy resources, including systems, resources, and users. The key objective of context awareness is to align attributes and to intensify couplings between different energy resources by decomposing and aggregating internal ontology models. Intertemporal and interspatial correlations of energy resources are made available by the cooperative transmission of ontology-based semantic contexts in the protocol framework. An informational architecture based on the conceptual energy tree finally can be established using incomplete measurement data and reasoning for large-scale industrial networks. A Smart Grid application instance is given to demonstrate the functionalities of energy tree dynamics.